Pebble dynamics and thermal-fluid analysis of high-temperature gas-cooled pebble bed reactors using DEM and CFD simulations - Mehta, Kashminder S.; Goddard, Braden; Wu, Zeyun (Frontiers in Nuclear Engineering, 2026)
This study presents a multiphysics computational simulation framework for analyzing pebble dynamics and thermal-fluid behavior in High-Temperature Gas-Cooled Pebble Bed Reactors (HTG-PBR). The pebble circulation and intermixing effects are predicted using Discrete Element Method (DEM) implemented in LIGGGHTS, while the thermal-fluid behavior is simulated with computational fluid dynamics (CFD) in OpenFOAM. The CFD model employs a porous-media formulation with a local thermal non-equilibrium model to capture the energy exchange between the helium coolant and pebbles. Integrating the DEM-based mixing effects into the porous CFD model enables a more physically representative and scalable approach for full-core reactor analysis. Both DEM and CFD solvers are validated using established pebble-bed benchmark problems to confirm the viability of the developed computational models. A HTG-PBR-like conical model reactor is employed as a test problem to evaluate the developed method. The simulation results confirm the predictive capability of the developed models for HTG-PBR performance analysis and provide insight for future multiphysics coupling strategies for reactor design optimization.